EFFECT OF CONCENTRATION OF UREA (AMMONIUM SULFATE) FERTILIZER ON MAKING NATA DE PINA FROM PINEAPPLE JUICE (ANANAS COMOSUS L. MERR) - Mulawi; Ayu Kristina (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
This study aims to explain the effect of the concentration of urea fertilizer (Ammonium Sulfate) on the manufacturing of Nata De Pina. This trial aims to compare different concentrations of urea (Ammonium Sulfate) fertilizer. The parameter observed was the weight of Nata De Pina. This research was conducted in six stages, namely: (1) preparing pineapple, (2) fineness, (3) cooking, (4) cooling, (5) addition of acetobacter xylinum and fermentation, (6) harvesting and measurement of Nata De Pina . Based on the research, it was produced that the way to make Nata De Pina can be done by preparing ripe pineapple fruit and cleaning it and then cutting it into small pieces and mashed using a blender to extract the pineapple juice. When blended, the ratio between pineapple and water is 1 kg of pineapple with 1 liter of water. Then, filtered to take water or pineapple juice. In addition, other ingredients are also used in the cooking process such as urea fertilizer (Ammonium Sulfate) with different concentrations, sugar, glacial acetic acid, and acetobacter xylinum bacteria. After all the ingredients have been prepared, then do the cooking with a small flame. If it boils, add all the other ingredients except the acetobacter xylinum bacterium and leave it for 2-3 minutes after which the baking sheet is prepared to cool down, when the Nata De Pina solution has cooled down, put in 10 ml of acetobacter xylinum bacteria. After that, the surface of the baking sheet is tightly closed using newspaper and allowed to stand for 14 days for the fermentation process to become a Nata De Pina product. Then the harvesting process of Nata De Pina is carried out and the weight is measured. Nata De Pina with greater weight parameters and good quality is shown in Nata De Pina with the highest concentration of urea (ammonium sulphate) fertilizer, which is 2.5 grams. So in this case, the concentration of urea (Ammonium Sulfate) fertilizer suitable for making Nata De Pina is 2.5 grams.